Mitigation of Salt Stress in Two Wheat Cultivars by Promising PGP Halotolerant Bacillus sp. Strain AE-EH1 Isolated from a Marine Environment - Eman Hamada; Adel Eltoukhy; Metwally K. Mahfouz; Abdel Kareem S.H. Mohamed (Novel Research in Microbiology Journal)
Soil salinity is a crucial challenge that restricts plant development and productivity. In this study, we aimed to report a promising marine-derived plant growth promoting (PGP) bacteria that can empower wheat plants to survive upon salt stress. Thirty-one bacterial isolates derived from marine environments were isolated and assessed for PGP activities. Among these tested isolates, a strain coded as AE-EH1 showed promising PGP activities. Based on the phenotypic characterization, using 16S rRNA gene sequencing, phylogenetic, and biochemical analyses, the selected isolate was identified as Bacillus sp. strain AE-EH1 and assigned an accession no. of OR144427. The target strain AE-EH1 could produce indole acetic acid, ammonia, and HCN, furthermore, it could fix atmospheric nitrogen and solubilize phosphate. Meanwhile, the AE-EH1 was characterized as a halotolerant bacterium with a tolerance limit of up to 15 % NaCl with optimum growth at 3 % NaCl. Interestingly, AE-EH1 showed a high in vitro antagonistic effect against 6 common plant pathogenic fungal species, including Botrytis fabae, B. cinerea, Fusarium oxysporum, Macrophomina phaseolina, Rhizoctonia solani, and Sclerotinia sclerotiorum. Inoculating, AE-EH1 into wheat cvs. Sakha 95 and Masr 3 under salt stress markedly improved the salt tolerance of these wheat cultivars. Moreover, fresh and dry weights of wheat cultivars had improved compared to non-treated plants as well as chlorophyll a, b, and carotenoids. Total carbohydrates, proteins, and lipids were increased in both Sakha 95 and Masr 3 cultivars as an influence of bacterial strain inoculation. Antioxidant peroxidase, catalase, and proline contents were accumulated in both wheat varieties. Our study provides a promising bacterial strain that can alleviate salt stress and enhance the growth and productivity of wheat under stress and normal conditions.